Eating behavior and body mass index in students from two Peruvian public universities - López-Ráez, Luz Eufemia (2024)
The objective was to relate eating habits with the body mass index and physical activity of university students. 237 students from the National University Federico Villarreal and 163 students from the National University of Engineering were surveyed in 2022, using an online form whose items were distributed in demographic data to characterize the students and their eating behavior (EB). Th e Likert scale was used. Th e data was analyzed with Microsoft Offi ce Excel updated to 2023. It was found that the average Body Mass Index (BMI) of the students is 24.5, falling within the normal classifi cation, they tend to eat more foods prepared at home, the Nutritional quality is subject to accessibility due to time and money; they usually consume lunch, omitting other meals. A low percentage considers they have Good eating habits. For the study group, physical activity was reduced during the development of their studies. Th e behavior of food selection by type of processing is similar for both sexes, with those with normal BMI giving priority to the intake of fresh and cooked foods.